Analgesic effect of pericapsular nerve group block on elderly patients undergoing hip replacement - Zhou, Min; Xu, Qiuping; Zuo, Dong; Wang, Zhiyi; Zhang, Maohua; Liu, Tingting; Liu, Renqi (Vojnosanitetski pregled, 2023)
Background/Aim. Pericapsular nerve group block (PNGB) does not affect the motor nerve while blocking the obturator and femoral nerves. The aim of the study was to determine the application value of PNGB for hip replacement in the elderly. Methods. Ninety elderly patients who underwent hip replacement from March 2019 to October 2020 were randomly divided into the fascia iliaca compartment block (FICB) group and the PNGB group. FICB and PNGB were performed prior to subarachnoid block (SAB). Their baseline data, operation conditions, incidence of adverse reactions, visual analog scale (VAS) score, heart rate (HR), mean arterial pressure (MAP), plasma cortisol (COR), and epinephrine (E) levels were compared. Results. VAS score, E, and plasma COR levels in the PNGB group were lower than those in the FICB group at time points T2–T4 (T2: 10 min after nerve block; T3: at position changing; T4: after position changing) (p < 0.001). There were no significant differences in HR and MAP between the two groups at any time point (p > 0.05). In the PNGB group, the ultrasonic imaging time was shorter, the time point of pressing patient-controlled analgesia (PCA) for the first time was later, and the numbers of pressing PCA were fewer than those of the FICB group (p < 0.001). No local anesthetic poisoning took place after the nerve block, and no hematoma at the puncture site, nerve injury, nausea and vomiting, dizziness, or delirium occurred. Conclusion. Both FICB and PNGB prior to SAB were highly safe for hip replacement in the elderly; however, PNGB has shorter ultrasonic imaging time, better analgesic effect, and milder oxidative stress, so it is worth applying it clinically.
Keywords: aged; analgesia; anesthesia, conduction; arthroplasty, replacement, hip; methods